(untitled) (The International Journal for Scientific Research, 2023)
Teaching students is nothing but a means of expression that depends on sounds, words, lines, and colours, and it is a means of liberating a person from fear and forming human bonds, which in turn is a means of building and integrating personality. If the student was allowed to express through drawing a situation that affected his attention or affected him, he produced a true picture of his feelings and feelings, so we conclude that the artwork is not a recording of real facts as much as it is a kind of expression The study of the drawings of isolated students is one of those areas, as it was necessary to take care of studying these drawings to identify the advantages that characterize their drawings. It enables them to adapt psychologically and socially.